What is social prescribing? - Kimberlee, Richard (Advances in Social Sciences Research Journal, 2015)
This article outlines research into social prescribing provision in one Clinical Commissioning Group area in England.  Based on primary data collected from focus groups with social prescribing  practitioners (n=8), local council/Public Health employees (n=6) and GPs (n=4) and interviews with  40 social prescription practitioners and 22 patients from 23 interventions it shows that there is no clear and agreed definition of what constitutes social prescribing. Based on analysis of local practice this article delineates social prescribing interventions into four types: Signposting, Light, Medium and Holistic. It outlines the problems related to data collection around social prescribing interventions effectiveness but points to emerging evidence that suggests that SP holistic interventions can contribute to improvement in patient wellbeing, reduction in anxiety and depression and attendance at GP surgeries.